2007
DOI: 10.1016/j.ccr.2007.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Controls Tumor Development in an Ink4a/Arf-Independent Manner in a Mouse Model for Glioma

Abstract: The Polycomb group and oncogene Bmi1 is required for the proliferation of various differentiated cells and for the self-renewal of stem cells and leukemic cancer stem cells. Repression of the Ink4a/Arf locus is a well described mechanism through which Bmi1 can exert its proliferative effects. However, we now demonstrate in an orthotopic transplantation model for glioma, a type of cancer harboring cancer stem cells, that Bmi1 is also required for tumor development in an Ink4a/Arf-independent manner. Tumors deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
213
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(233 citation statements)
references
References 57 publications
17
213
2
Order By: Relevance
“…Bmi1 is a well-known repressor of p16INK4a and, in some cases, such as in mammalian cells, p14ARF genes (Jacobs et al, 1999;Molofsky et al, 2006). However, several previous reports have indicated that there could be another important Bmi1 target gene, especially in the nervous system, in addition to p16INK4a/p14ARF (Jacobs et al, 1999;Bruggeman et al, 2007). In our study, Bmi1 overexpression accelerated the proliferation of several NB cell lines, although p14ARF/ p16INK4a repression was not so obvious (Figure 4).…”
Section: Mycn-induced Bmi1 Represses Tumor Suppressors H Ochiai Et Alcontrasting
confidence: 43%
“…Bmi1 is a well-known repressor of p16INK4a and, in some cases, such as in mammalian cells, p14ARF genes (Jacobs et al, 1999;Molofsky et al, 2006). However, several previous reports have indicated that there could be another important Bmi1 target gene, especially in the nervous system, in addition to p16INK4a/p14ARF (Jacobs et al, 1999;Bruggeman et al, 2007). In our study, Bmi1 overexpression accelerated the proliferation of several NB cell lines, although p14ARF/ p16INK4a repression was not so obvious (Figure 4).…”
Section: Mycn-induced Bmi1 Represses Tumor Suppressors H Ochiai Et Alcontrasting
confidence: 43%
“…Consistently, BMI1 also controls the differentiation potential of adult NSCs (Zencak et al, 2005;Bruggeman et al, 2007). In young adult mice, constitutive deletion of Bmi1 triggers increased glial cell production in vivo (Zencak et al, 2005) and decreased neurogenic capacity of cultured adult NSCs after serial passaging (Bruggeman et al, 2007).…”
Section: Chromatin Modifiers In Aging Stem Cellsmentioning
confidence: 78%
“…Consistently, BMI1 also controls the differentiation potential of adult NSCs (Zencak et al, 2005;Bruggeman et al, 2007). In young adult mice, constitutive deletion of Bmi1 triggers increased glial cell production in vivo (Zencak et al, 2005) and decreased neurogenic capacity of cultured adult NSCs after serial passaging (Bruggeman et al, 2007). This increase in astrocytes phenocopies the increase in astrocyte production known to occur in the brain during aging (Bondolfi et al, 2004), raising the possibility that altered activity of BMI1 during aging contributes to a loss of stem cell multipotency.…”
Section: Chromatin Modifiers In Aging Stem Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…Of interest, an Ink4a/Arf-independent contribution of Bmi1 to not only self-renewal in neural stem cells but also tumorigenesis in a mouse model for glioma has been reported. 27,28 The current in vivo transplant assays ascertained that Bmi1-transduced Ink4a/Arf À/À Dlk þ cells but not control Ink4a/Arf À/À Dlk þ cells acquire tumorigenic potential. Bmi1-transduced Ink4a/Arf À/À Dlk þ cells showed an augmented self-renewal capability as evident from the higher replating efficiency in the single cell-sorting analysis compared to Ink4a/Arf À/À Dlk þ cells.…”
Section: Discussionmentioning
confidence: 98%